What do children observe and learn from televised sports betting advertisements? A qualitative study among Australian children - Hannah Pitt; Samantha L. Thomas; Amy Bestman; Mike Daube; Jeffrey Derevensky (Elsevier, 2017)
Abstract Objective: To explore children's awareness of sports betting advertising and how this advertising may influence children's attitudes, product knowledge and desire to try sports betting. Methods: Semi‐structured qualitative interviews were conducted with 48 children (8-16 years) from Melbourne, Victoria. The interview schedule explored children's recall and interpretations of sports betting advertising, strategies within advertisements that may appeal to children, children's product knowledge and understanding of betting terminology, and factors that may encourage gambling. Interviews were transcribed and thematic analysis was conducted. Results: Children recalled in detail sports betting advertisements that they had seen, with humour the most engaging appeal strategy. They were also able to describe other specific appeal strategies and link these strategies to betting brands. Many children described how advertisements demonstrated how someone would place a bet, with some children recalling the detailed technical language associated with betting. Conclusions: Children had detailed recall of sports betting advertisements and an extensive knowledge of sports betting products and terminology. Implications for public health: To protect children from the potential harms associated with sports betting, governments should consider changing regulations and implementing evidence‐based education campaigns to counter the positive messages children receive from the sports betting industry.